Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1177/107602960300900410
|View full text |Cite
|
Sign up to set email alerts
|

A Trend of Platelet Indices in Patients with Green Pit Viper Toxin

Abstract: The green pit viper (Trimeresurus albolabris and Trimeresurus macrops) is a common venomous snake in Thailand. The green pit viper venom has major effects on the hematologic system. The venom is found to have a thrombin-like effect in vitro but cause a defibrination syndrome in vivo. Unlike other pit viper snakes (such as Malayan pit viper and Russel's pit viper), the venomous effect on red blood cells is rarely mentioned. Clinical features of venomous snake bites vary from asymptomatic to fatal bleeding. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…25 It was shown in both in vivo and in vitro tests that the venom of the white-lipped green pit viper ( Trimeresurus albolabris ) in Thailand has a direct effect on platelets by decreasing mean platelet volume and the number. 26,27 The venom of this snake also has major effects on red blood cells by decreasing mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration. 28 In hump-nosed pit viper bites Rathnayaka et al also observed reduction of mean corpuscular volume in 11.7%, decreased mean corpuscular hemoglobin in 18.4%, reduced mean corpuscular hemoglobin concentration in 9%, and reduction of mean platelet volume in 6.5% of envenomed patients.…”
Section: Discussionmentioning
confidence: 99%
“…25 It was shown in both in vivo and in vitro tests that the venom of the white-lipped green pit viper ( Trimeresurus albolabris ) in Thailand has a direct effect on platelets by decreasing mean platelet volume and the number. 26,27 The venom of this snake also has major effects on red blood cells by decreasing mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration. 28 In hump-nosed pit viper bites Rathnayaka et al also observed reduction of mean corpuscular volume in 11.7%, decreased mean corpuscular hemoglobin in 18.4%, reduced mean corpuscular hemoglobin concentration in 9%, and reduction of mean platelet volume in 6.5% of envenomed patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 Another study demonstrated that platelet count and MPV were significantly lower in envenomated blood samples compared to the healthy group. 27 To the best of our knowledge, there have been no previous studies evaluating PDW and PDWLR in snakebite envenomation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the risk of systemic bleeding, this patient did not undergo sufficient investigations to assess the possible evolution of systemic coagulopathy. Although thrombocytopenia is a common hematological effect and a hallmark of hematological disorders due to pit viper envenomation, 23,36 38 platelets were only measured in a single assay that detected mild thrombocytopenia (Table 1). For the proper diagnosis of pit viper bite, platelets should be measured on arrival and serially monitored including for a week or more postdischarge.…”
Section: Discussionmentioning
confidence: 99%